5PSQ-157 Expenditure and consumption descriptive analysis: rituximab originator versus biosimilar in an Italian district. (14th March 2021) - Parola, BMA; Alemanno, S; Capilli, M; Colasanto, I; Fiorentino, D; Marcato, M; Pestrin, L; Strobino, S; Varese, A; Viglione, E; Brunitto, G
Abstract : Background and importance: The introduction of biological drugs changed the pharmaceutical market, improving patients' prognoses and quality of life. Intravenous MabThera, authorised in January 1998, is the originator of the monoclonal antibody rituximab. In Italy, the regulatory agency approved the first rituximab biosimilar, Truxima, in July 2014, and the second, Rixathon, in December 2017. Aim and objectives: The objective was to analyse and compare MabThera and its biosimilars in our region in the period 2017–2019 in terms of regional consumption, costs and adverse drug reactions (ADRs). Material and methods: Regional consumption and costs data for rituximab between January and September 2017, 2018 and 2019 were collected and analysed, using Microsoft. ADR reports were extracted from the Adverse Drug Reactions National Report (ADRsNR) and stratified by gravity, gender of the patient and diagnosis. Results: In 2017, the number of intravenous MabThera dispensed packs was 10 017, with a progressive reduction over the years (552 in 2019). Truxima decreased from 2274 delivered packs in 2018 to 117 in 2019; Rixathon increased from 3491 in 2018 to 9259 in 2019. Intravenous distributed pack numbers of MabThera decreased from 2017 to 2019 and was about −94.49%. Regarding costs, MabThera expenditure in 2017 was about 9 902 232.64€, in 2018 it was 3 590 428.00€ and in 2019 it was 613 502.88€. Truxima costs were 2 027 695.38€ in 2018 and 91 438.67€ in 2019. Rixathon expenditure was 2 066 974.79€ in 2018 and 5 473 728.71€ in 2019. A reduction of 93.80% was registered for MabThera expenditure from 2017 to 2019. From January 2002 to March 2020, ADRsNR rituximab ADRs were 2865: 10.23% MabThera, 19.02% Truxima and 10.66% Rixathon. 50.3% of patients were men and 49.7% women. ADR gravity was 2.2% deaths, 39.1% serious and 57.8% not serious. Diagnoses principally concerned itch 7.9%, dyspnoea 7%, neutropenia 7.3% and pyrexia 7%. Conclusion and relevance: ADRsNR biosimilar data are still limited: greater collaboration between health professionals is needed to structure a system of more robust and adequate pharmacovigilance, to overcome the information gap relating to the security of the originator and biosimilar. Nonetheless, biosimilar drugs are a valid therapeutic alternative for patients, and a good way to reduce expenditure and to optimise available resources, ensuring good pharmaceutical governance. Biosimilar switch involves a multidisciplinary team composed by prescribers and pharmacists. Pharmacovigilance is important to discover and characterise ADRs in the post-marketing phase. References and/or acknowledgements: Conflict of interest: No conflict of interest